Exploring Audience Perception on the Impacts of Religo-Culturo-Contextual Factors (RCCF) on Newspaper Salience and Framing of Child Defilement in Osun State (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study explored audience perception on the impacts of Religo-Culturo-Contextual Factors (RCCF) on Newspaper Salience and Framing of Child Defilement in Osun state. This study was anchored on Social Judgement Theory (SJT). This study employed a qualitative research design using in-depth interviews to explore audience perception on how Religo-Culturo-Contextual Factors (RCCF) influence newspaper salience and framing of child defilement. Purposive and Convenient Sampling techniques were used to select 15 participants who were knowledgeable about the issue and could provide insights on the focus of this study. Results showed three recurrent themes which are; selective media attention, victim-blaming, and diminished public awareness. The findings revealed that RCCF strongly influence which child defilement cases are covered by newspapers and how prominently they are reported to the media. Participants indicated that newspapers often give less attention to cases involving influential community or religious figures. Also, it was found that inadequate and biased media coverage discourages families from seeking justice for child defilement, as the crime is often framed as private or less severe matter with blames on the victims at times. This study recommend that newspapers should adopt more balanced and sensitive rather than reinforcing cultural and religious biases. Also, journalists in Osun State should be trained to recognize and counteract RCCF in their reporting to ensure that all child defilement cases receive fair and consistent coverage. Lastly, media organizations should collaborate with NGOs to raise awareness about the legal and human rights dimensions of child defilement to counter RCCF-driven narratives that stigmatize victims.